Meaning and purpose in Huntington's disease: a longitudinal study of its impact on quality of life. Issue 8 (20th July 2021) - Sokol, Leonard L.; Troost, Jonathan P.; Kluger, Benzi M.; Applebaum, Allison J.; Paulsen, Jane S.; Bega, Danny; Frank, Samuel; Hauser, Joshua M.; Boileau, Nicholas R.; Depp, Colin A.; Cella, David; Carlozzi, Noelle E.
Abstract: Objective: Previous work in Huntington's disease (HD) has shown that a sense of meaning and purpose (M&P) is positively associated with positive affect and well‐being (PAW); however, it was unknown whether HD‐validated patient‐reported outcomes (PROs) influence this association and how M&P impacts PROs in the future. Our study was designed to examine if HD‐validated PROs moderate the relationship between M&P and PAW and to evaluate if baseline M&P predicts 12‐ and 24‐month changes in HD‐validated PROs. Methods: This was a longitudinal, multicenter study to develop several PROs (e.g., specific for the physical, emotional, cognitive, and social domains) for people with HD (HDQLIFE). The sample consisted of 322 people with HD ( n = 50 prodromal, n = 171 early‐stage manifest, and n = 101 late‐stage manifest HD). A single, multivariate linear mixed‐effects model was performed with PAW as the outcome predicted by main effects for M&P and several moderators (i.e., an HD‐validated PRO) and interactions between M&P and a given PRO. Linear‐mixed models were also used to assess if baseline M&P predicted HD‐validated PROs at 12 and 24 months. Results: Higher M&P was positively associated with higher PAW regardless of the magnitude of symptom burden, as represented by HD‐validated PROs, and independent of disease stage. In our primary analysis, baseline M&P predicted increased PAW and decreased depression, anxiety, anger, emotional/behavioral disruptions, and cognitive decline at 12 and 24 months across all disease stages. Interpretation: These findings parallel those seen in the oncology population and have implications for adapting and developing psychotherapeutic and palliative HD interventions.